Medicinal ethnobotany of the Yakkha community in eastern Nepal - Dewan, Karun; Shrestha, Nawal; Sapkota, Ramesh; Rai, Jeevan; Lama, Smritee; Shrestha, Bharat Babu (Ethnobotany Research and Applications, 2023)
Background: In rural Nepal, a significant population relies on traditional medicinal treatments for their healthcare needs. However, little is known about the ethnobotanical practices of the Yakkha people, a distinct Tibeto-Burman ethnic group following the Kirati religion in Sankhuwasabha district in eastern Nepal. This study examines the use of medicinal plants by the Yakkha community in three remote villages and assesses the ethnobotanical significance of their traditional knowledge. Methods: The research was conducted in three Yakkha communities with varying levels of modernization, and Yakkha ethnic concentration. Data collection included key informant interviews, informal and structured interviews, focus group discussions, as well as direct and participatory observations. The Informant consensus factor was used to validate knowledge homogeneity. Results: The study documented 200 medicinal plant species and one fungus species, from 174 genera and 87 families, utilized by the Yakkha people to treat 75 human ailments. Above-ground vegetative parts (34%), reproductive (32%), below-ground (27%), and whole plants (7%) were the main plant parts used for medicinal purposes, primarily administered orally. While no new medicinal plant species were discovered, a few species (n = 10) revealed novel uses. Informant consensus was high for Musculoskeletal, Circulatory, and Nervous system disorders. Conclusions: The Yakkha community in Sankhuwasabha district possesses valuable traditional knowledge of medicinal plant utilization, with strong consensus among locals. The diverse range of medicinal plant use underscores their effectiveness in treating various ailments. Exploring the bioactive compounds in these plants could lead to the discovery of novel medicines for critical human diseases. Keywords: Ethnobotany, Himalayan medicine, Kirat, Sankhuwasabha, Tibeto-Burman ethnic group.